The Role of Digital Supply Chain Management Practices in the Relationship between Organizational Culture and Customer Development - Awain, Ali Mohsin Salim Ba; Sulaiman, Mohammed Ali Bait Ali; Al Sheyadi, Anwar; Sukati, Inda (Journal of Ecohumanism, 2024)
Through Digital Supply Chain Management Practices (DSCMP), this study investigates the relationship between organizational culture (OC) and customer development (CD), taking into account both direct and indirect influences. Data from 214 respondents who have registered in Indonesia's Riau Islands Province were analysed statistically. The results showed that CD was positively impacted by OC and DSCMP. Additionally, the connection between OC and CD was found to be mediated by DSCMP. Two crucial facilitators for growing a company's clientele in digital supply chains (SC) are DSCMP and OC. Using the Resource Dependency Theory (RDT) as a basis. This study discovered that in order to increase the firm's efficiency, digitalization-related SCMP capabilities need to be developed internally. Organizational leaders (OL), organizational glue (OG), dominating characteristics (DC), and strategic focus (SE) should all be integral parts of DSCMP in organizations.